2023
DOI: 10.3390/rs15081981
|View full text |Cite
|
Sign up to set email alerts
|

Rockfall Magnitude-Frequency Relationship Based on Multi-Source Data from Monitoring and Inventory

Abstract: Quantitative hazard analysis of rockfalls is a fundamental tool for sustainable risk management, even more so in places where the preservation of natural heritage and people’s safety must find the right balance. The first step consists in determining the magnitude-frequency relationship, which corresponds to the apparently simple question: how big and how often will a rockfall be detached from anywhere in the cliff? However, there is usually only scarce data on past activity from which to derive a quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…We observed variations in the scaling exponent from 0.5 to 1.3 on a month-to-month basis, with one anomalous value over 2.5. This variability is generally consistent with the findings of Janeras et al [45], who showed a fluctuation of the scaling exponent from about 0.25 to 0.81 at one location and from about 0.38 to 0.78 at another location, although their rockfall database monitoring intervals were in the order of a year rather than monthly. Both of these findings show that rockfall hazard is not constant through time over all time intervals.…”
Section: Spatiotemporal Resolution Considerations For Rockfall Monito...supporting
confidence: 91%
“…We observed variations in the scaling exponent from 0.5 to 1.3 on a month-to-month basis, with one anomalous value over 2.5. This variability is generally consistent with the findings of Janeras et al [45], who showed a fluctuation of the scaling exponent from about 0.25 to 0.81 at one location and from about 0.38 to 0.78 at another location, although their rockfall database monitoring intervals were in the order of a year rather than monthly. Both of these findings show that rockfall hazard is not constant through time over all time intervals.…”
Section: Spatiotemporal Resolution Considerations For Rockfall Monito...supporting
confidence: 91%
“…As shown in Figure 7, cumulative rockfall magnitude-frequency plots relatively linearly on a log-log graph over three (Sites B and D), four (Site C), or five (Site A) orders of magnitude, an effect that is similarly observed in rockfall inventories collected by other researchers [20][21][22][23][24][25]34,36]. This observation indicates that rockfall at the study sites follows a power-law magnitude-frequency distribution, as observed frequently in nature.…”
Section: General Inferences From the Rockfall Inventorysupporting
confidence: 76%
“…The statistical analysis of an inventory of past mass-wasting events is a rigorous method to inform models that project the future likelihood of mass-wasting [17]. Masswasting events, such as landslides and rockfalls, have been shown to self-organize into a power-law magnitude-frequency distribution [18][19][20][21][22][23][24]. Researchers have recently compiled lidar-based inventories of hundreds to thousands of rockfall events over multi-year periods [20][21][22][23][24][25][26] that have demonstrated power-law magnitude-frequency relationships over several orders of magnitude.…”
Section: Lidar-based Rockfall Inventory Development and Utilizationmentioning
confidence: 99%
See 2 more Smart Citations